Biological Characteristics of Captive Chinese Wuzhishan Minipigs (Sus scrofa). (20th August 2014) - Min, Fangui; Pan, Jinchun; Wang, Xilong; Chen, Rui'ai; Wang, Fengguo; Luo, Shuming; Ye, Jiancong
Abstract : In order to meet the demands of experimental minipigs for biomedical researches, we have aimed at cultivating grazing Chinese Wuzhishan (WZS) minipigs and trying to make them useful and affordable since the 1990s. After more than ten years of captive cultivation following sound management practices and a rigorous selection program for fertility and litter size, we established an outbred WZS minipigs colony with a core group (14 males and 30 females) and an expanding group (20 males and 40 females). In 2010–2013 periods, extensive background data of this colony were recorded and analyzed. This paper was written to provide pertinent information about outbred WZS minipigs for producers, users, and others concerned with WZS minipigs. It contains physical characteristics, growth performance, productive performance, hematology and blood biochemistry, microsatellite analysis, organ coefficients, and carcass properties. Results show that WZS minipigs have characteristics of small body size, slow growth rate, long life cycle, high reproductive rate, and maintaining original genetic diversity. All data present that outbred WZS minipigs are suitable laboratory animal and model animal.